Григорій Сковорода і дискурс українського модернізму - Криса, Б. (Слово і Час, 2022)
У статті здійснено спробу дослідити одну з тенденцій раннього модерну, яка увиразнюється у творчості Григорія Сковороди поєднанням християнської концепції людського життя з досвідом античності, сприйнятим крізь призму християнства. У цьому контексті мотив духовного оновлення безпосередньо зумовлений розумінням співдії Божого Слова зі словом людським, що виявляється у наполегливій праці над розкриттям біблійного сенсу і над творенням нової форми для його збереження й передання. У такий спосіб стверджується позачасовий характер людського ідеалу та його функція в розрізненні часових форм нового і старого, справжнього й несправжнього. Відзначено суголосність концептів та образів Г. Сковороди з теоріями модернізму й модерної ідентичності ХХ і початку ХХІ ст., що дозволяє розглядати його тексти не лише з погляду своєрідної кристалізації ідей, але також як чинник новочасної української літератури. The aim of the paper is to explore the line of Ukrainian Modernity which is expressed in the writings of Hryhorii Skovoroda by combining the Christian concept of human life and the experience of Antiquity, perceived through the prism of Christianity. In this context, the motive of spiritual renewal is directly conditioned by the understanding of the interaction of God’s Word with the human one, which is manifested in the persistent work of revealing the biblical meaning and creating a new form for its preservation and transmission. In this way, the timeless nature of the human ideal and its function in distinguishing the temporal forms of the new and the old, the real and the false, is affirmed. It is noticed that Skovoroda’s concepts and images agree with the theories of modernism and modern identity of the 20th and early 21st centuries. Against the background of the elongated, even irritating discourse of Ukrainian Modernism caused by external and internal transformations of national existence, Skovoroda’s markers prove that spiritual, moral, and expressive priorities may be conflicting but not deny each other. This is mostly true for language and correlation of religion and metaphysics. According to Skovoroda, the art of the form serves as a shell, amulet, and translator of the divine meaning revealing life-giving depths. In this sense, the whimsical clothing of the word draws attention to the process of cognition, gives an opportunity to see the inner behind the external. In this regard, the continuity between the Baroque and Romanticism determines primarily their common spiritual space, due to the whirlpool of the same sources. It is concluded that Skovoroda’s creative figure always becomes a landmark for Ukrainian Modernism, because due to him even modernity is understood not only as a certain era or ideology but as the inner state and inner world of an author. This state can coexist with the patriarchal way of life and with the phenomena of real or conditional progress. In this sense, the thesis of the unfinished project of Ukrainian modernism must be understood from the perspective of eternal travel and distant horizons, which may not always equally reveal but do equally contain sources of Antiquity and Christianity.